2023
DOI: 10.1039/d2ma00872f
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of incorporating Cu+and Cu2+ions into silicate bioactive glasses using molecular dynamics simulations

Abstract: Copper oxide containing bioactive glasses have drawn attention because of their unique properties as biomaterial for targeted tissue engineering applications. This is due to their ability in acting as stimulants...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…The solutions of metal cations, including Na + , K + , Mg 2+ , Ca 2+ , Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , Zn 2+ , Cd 2+ , Cr 3+ , Al 3+ and Fe 3+ , were prepared from their nitrate salts in MeCN. 1 H NMR spectrum was taken on a JEOL JNM-ECS 400M spectrometer. Chemical shifts (δ) are reported in ppm, relative to tetramethylsilane.…”
Section: General Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions of metal cations, including Na + , K + , Mg 2+ , Ca 2+ , Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , Zn 2+ , Cd 2+ , Cr 3+ , Al 3+ and Fe 3+ , were prepared from their nitrate salts in MeCN. 1 H NMR spectrum was taken on a JEOL JNM-ECS 400M spectrometer. Chemical shifts (δ) are reported in ppm, relative to tetramethylsilane.…”
Section: General Informationmentioning
confidence: 99%
“…Cupric salts are widely employed for wood and leather treatment, plant disease, and water treatment. Moreover, copper(II) cations (Cu 2+ ), as a cofactor and/or structural component of various enzymes, are involved in many physiological pathways [1]. The fundamental research on Cu 2+ detection is crucial to environmental monitoring and biological research.…”
Section: Introductionmentioning
confidence: 99%
“…They exist in two forms: Cuprous oxide (Cu2O) and Cupric oxide (CuO), each possessing distinct colors, crystal structures, and physical properties. The oxidation state of copper (Cu) determines the chemistry of these oxides, with Cu2O containing Cu + and CuO containing Cu 2+ [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although copper is recognized for its pivotal role in hemostasis and bone formation, an excess amount of this element can be cytotoxic [36]. Studies have reported that the body tolerates low doses of copper, typically up to 8.66 mg kg −1 , while doses ranging from 50 to 54.4 mg kg −1 can be lethal due to the generation of free radicals, resulting in toxicity and inflammatory effects [36][37][38].…”
Section: Introductionmentioning
confidence: 99%